Social networks as the new frontier of terrorism: #terror - Scaife, Laura (Routledge research in IT and e-Commerce law, 2017)
Man's terrorist is another man's facebook friend -- Terrorism's love affair with social media -- Freedom of the newsfeed -- The spy who liked my tweet : counter-intelligence and the terrorists' reaction to Snowden -- Let's start a war -- National security and the fourth estate in a brave new social media world